Accuracy of The Level of Critical Water Catchment Area for Flood Mitigation Around Bengkulu City, Indonesia - Bambang Sulistyo; Hery Suhartoyo; Teguh Adiprasetyo; Kanang Setyo Hindarto; Noviyanti Listyaningrum (Faculty of Geography, Universitas Gadjah Mada, 2021)
Disaster mitigation activities require the availability of a potentially flooded area (PFA) map. One of the causes of flooding is the criticality of water catchment areas; the higher the criticality level, the higher the flooding potential. This study aims to determine the accuracy of the model for determining the PFA around Bengkulu City, which was derived from the Level of Critical Water Catchment Area (LCWCA) model developed by the Ministry of Forestry. After obtaining the LCWCA Map, another analysis was performed in order to obtain the PFA Map. Furthermore, the overlaying was carried out with the Existing Flood Map in such a way that the level of accuracy is known. The threshold values from Justice are used to justify the level of accuracy in three categories, namely Good (> 85%), Moderate (70 - 85%), and Poor (<70%). The results showed that in the eight sub-watersheds around the city of Bengkulu, there were two sub-watersheds with reasonable accuracy (> 85%), which means that there was > 85% overlap between areas on the Potentially Flooded Area Map as a result of the analysis of The LCWCA with the area on the Existing Flood Map. There are three sub-watersheds with Moderate accuracy (70 - 85%) and three sub-watersheds with Poor accuracy (<70%)